Derivation of Inter-Atomic Force Constants of Cu2O from Diffuse Neutron Scattering Measurement - T. Makhsun; T. Sakuma; E. Kartini; R. Sakai; H. Takahashi; N. Igawa; S.A. Danilkin (Atom Indonesia, 2013)
Neutron scattering intensity from Cu2O compound has been measured at 10 K and 295 K with High Resolution Powder Diffractometer at JRR-3 JAEA. The oscillatory diffuse scattering related to correlations among thermal displacements of atoms was observed at 295 K. The correlation parameters were determined from the observed diffuse scattering intensity at 10 and 295 K. The force constants between the neighboring atoms in Cu2O were estimated from the correlation parameters and compared to those of Ag2O.Received: 16 January 2013; Revised: 10 April 2013; Accepted: 15 April 2013